Is the Regional Perspective Useful? Rural and Urban Quality of Life: an Assessment - Annette Spellerberg; Denis Huschka; Roland Habich (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In Germany, processes can be observed that have long been out of keeping with the principle of equality of opportunity. Unemployment is concentrated in the structurally weak peripheral areas, in Eastern Germany in particular; emigration of young and better-educated people to the West is not diminishing, but contrary to expectation is again on the increase; aging processes have set in already, and when it comes to the provision of infrastructure, e.g. in the field of professional training, some regions are already suffering from considerable problems. These difficulties are frequently interpreted as differences between East and West and are explained away as problems resulting from reunification, such as the deindustrialization and restructuring of the economy and the enormous decline in the birth rate in Eastern Germany. Although these problems cannot just be attributed to social transformation and the birth rate crisis alone, being subject to more general processes of intensified globalization and the aging of society, the increasing regional disparities are rarely considered in the overall context of regional development patterns throughout Germany. Moreover, the difficulty of even obtaining data for purposes of comparison generally means that an international yardstick is lacking when regional developments are analyzed. The present study investigates regional disparities over a period of time in the light of subjective and objective indicators of the quality of life for individuals. To this end, we make use of data from the Wohlfahrtssurvey [Welfare Survey] from 1978 to 2001, among other sources. On the basis of the Euromodule that has been established at the WZB, we compare current regional patterns in Germany with those in other European countries. This approach makes it possible to provide information on the scale of regional disparities in various different countries, and to identify privileged and handicapped regions with reference to standards of living and the sense of wellbeing. The study's findings show that, in the past twenty-five years, welfare in Western Germany has evened out at a higher level, but currently a trend towards increasing economic disparity is discernible. In comparison with other European countries, on the other hand, the differences (regional differences) within Germany are comparatively slight.
Keywords: 330